PENGARUH PENAMBAHAN TITONIA TERHADAP SIFAT KIMIA ULTISOL DAN HASIL TANAMAN KEDELAI PADA MUSIM TANAM KE TIGA - Nurhajati Hakim; Herviyanti Herviyanti; Armi Meirita (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2006)
Last researches reported that Tithonia diversifolia (Mexican sunflower) could replace 25% to 50% of N and K of commercial fertilizer applied in ginger and maize production on the first and second season planting time respectively in the Ultisols of West Sumatra. A subsequent experiments were conducted to find out the the appropriate NK combination sources should be added on the third season to get high yield of soybean. The treatments were 8 combinations of NK-T. diversifolia + N + K commercial fertilizer for growing soybean such as A(0); B(0); C (25 kg NK+25 kg N+100 kg K); D (25 kg NK+ 25 kg N+100 kg K); E (50 kg NK+37,5 kg N+150 kg K); F(50 kg NK+37,5 kg N+150 kg K); G(100kg N K+25 kg N+100 kg K); and H(100 kg NK+ 25 kg N+100 kg K). The results showed that integrated use 25 kg NK from tithonia and 25kg N + 100kg K from commercial fertilizer (treatment C ) was an appropriate NK combination to get high yield of soybean (0,986 ton ha-1) on the third season in Ultisols, if on the first season ginger have been fertilized as 25% + 75% and on the second season maize have been fertilized as much 50% + 50% of NK from tithonia and NK from commercial fertilizer.Key Words : Thitonia, Ultisol, green manure